Effects of Carbon Content, Annealing Condition and Internal Defects on the nucleation, growth and coarsening of P-type Carbides in High Niobium Containing TiAl Alloys. Issue 1760 (30th December 2014) - Baker, I.; Heilmaier, M.; Kishida, K.; Mills, M.; Miura, S.; Wang, Li; Pyczak, Florian; Gabrisch, Heike; Lorenz, Uwe; MÃ¼nch, Mathias; Schimansky, Frank-Peter; Schreyer, Andreas; et al.
ABSTRACT The nucleation, growth and coarsening of carbides is investigated in high niobium containing TiAl alloys by diffraction and transmission electron microscopy. Higher carbon content increases the dissolution temperature of carbides. The solubility of carbon is much higher in a Î³/Î±2-phase alloy than in the Î³ phase alone. Hereby no significant influence of Nb on carbon solubility is found. Crystallographic defects as grain boundaries and dislocations promote carbide nucleation which results in a carbide precipitation sequence starting first at grain boundaries, then at dislocations and only later in the Î³ matrix away from crystallographic defects. The consumption of carbon by grain boundary carbides or neighboring Î±2 grains also generates a precipitate free zone in Î³ grains near the grain boundary.